2003
DOI: 10.1063/1.1570930
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic study of ferrimagnetic FeCr2S4: Evidence for low temperature structural transformations

Abstract: The elastic properties of single crystalline FeCr2S4 have been investigated as a function of temperature and magnetic field. The temperature dependence of the sound velocity is characterized by three distinct anomalies, namely at the Curie temperature TC=167 K, at T∼60 K, and at T∼15 K. For T<TC the sound velocity and, thus, the shear modulus depend on the magnetic field. The concurrence of elastic and magnetic anomalies in the ferrimagnetic state suggests that they are of a common origin. From the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
3
17
2
Order By: Relevance
“…24 Later on, ultrasonic studies indicated an anomaly in the temperature dependence of the shear modulus close to 60 K, and it was suggested that the onset of orbital order induces a structural distortion at this temperature. 25 This result, however, is hardly compatible with the observation that orbital order is established in polycrystals close to 10 K, while an orbital glass state is found in single crystals.…”
Section: 14contrasting
confidence: 48%
See 2 more Smart Citations
“…24 Later on, ultrasonic studies indicated an anomaly in the temperature dependence of the shear modulus close to 60 K, and it was suggested that the onset of orbital order induces a structural distortion at this temperature. 25 This result, however, is hardly compatible with the observation that orbital order is established in polycrystals close to 10 K, while an orbital glass state is found in single crystals.…”
Section: 14contrasting
confidence: 48%
“…the appearance of the cusps in the damping constants may be connected to domain reorientation processes visible in the ac susceptibility 24 and anomalies detected by ultrasonic investigations. 25 Although the absence of significant changes of the phonon frequencies contradicts the scenario of a structural phase transition at 60 K driven by orbital ordering as suggested in Ref. 25, it becomes clear that the complex mechanisms dominating the damping effects demand further theoretical studies to single out the important contributions in detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spin glass like magnetic transition were also observed at T g $ 60 K for x ¼ 0 and T g $ 45 K for x ¼ 0:5; respectively. Below T g ; differences between zero-field cooled (ZFC) and field cooled (FC) magnetization clearly appear in H ¼ 0:03 T: This spin glass like irreversible magnetic behavior would be attributed to the correlated Fe 3d orbital ordering [6]. This magnetic behavior for FeCr 2 S 4 is in good agreement with the previous reports [7][8][9][10].…”
supporting
confidence: 85%
“…Notably there occurs a drop in magnetization in the same temperature range [12], yet no significant change in entropy is derived from heat capacity [12]. There is some indication from TEM for a structural change [14] and an anomaly in ultrasound velocity both occurring around 60 K [15].…”
Section: Introductionmentioning
confidence: 94%